(untitled) (Research Nepal Journal of Development Studies, 2019)
This research was an attempt to take a deeper look at people’s experience of existing financial services and their providers. In addition, it aimed to identify definitive indicators that would help to create a roadmap for the delivery of effective financial services in Nepal. The study emphasized that ensuring financial inclusion is an arduous task and requires a holistic approach encompassing strategies for awareness raising, financial education, technical advice on different dimensions of money management, debt counseling, saving mobilization, provision of affordable credit services, research and development. In order to promote financial inclusion, there is a need to develop and apply specific strategies to expand the outreach of their services using combinations of lending methodologies, market led approaches to new product development, fostering linkages with local communities and promoting the use of technologies. This paper is basically descriptive and analytical in nature and based on a number of policy models and provisions formulated in recent years for promoting financial inclusion in Nepal. Secondary data is used, drawn primarily from, Poverty Alleviation Fund, Department of Co-operatives and different departments. Micro finance institutions should give equal priority for non-financial services such as financial literacy and provision of entrepreneurship skills through government and non-government organizations that ultimately helps to utilize micro-credit into productive sectors.